Role of NRF2 in protection of the gastrointestinal tract against oxidative stress - Yanaka, Akinori (J Clin Biochem Nutr, 2018)
The gastrointestinal tract is exposed to a variety of noxious factors, such as Helicobacter pylori, nonsteroidal anti-inflammatory drugs, gastric acid, ischemia-reperfusion, and mental stresses. Theses stressors generate free radicals within gastrointestinal tissues, causing organ injury and functional disturbance. Although the gastrointestinal tract can withstand such oxidative stresses to some extent by enhancing its antioxidant system via nuclear factor erythroid 2-related factor 2-Kelch-like erythroid cell-derived protein with CNC homology-associated protein 1-mediated pathways, acute or chronic exposure to oxidative stress can cause several gastrointestinal tract disorders, such as inflammation, ulcers, cancers, and various functional disturbances. Recent studies have demonstrated that some natural compounds and drugs can upregulate the nuclear factor erythroid 2-related factor 2-mediated antioxidant system, ameliorating or preventing these disorders. Although these compounds may be useful as chemopreventive agents, sufficient evidence for their clinical efficacy has not yet been provided. In addition, it is important to note that excessive nuclear factor erythroid 2-related factor 2 stimulation can be harmful to human health, especially from the standpoint of tumor biology.